Ekuivalensi Leksikal Dan Analisis Komponen Makna Penerjemahan Alat-Alat Doraemon Pada Manga Daich?hen Doraemon Karya Fujiko F Fujio - Emeralda Gianina Tumewu, Olivia; Gorethy Nie Nie, Maria; Oeinada, I Gede (Humanis, 2016)
This research is aimed to find out the lexical equivalence and whether meaning shift occurred or not in the Doraemon tools translation in volume 1-8 of Daich?hen Doraemon comics by Fujiko F Fujio and its translation in Indonesian by Hiromi Amadio Prabowo. The data were analyzed using qualitative analysis method. This research used the theory of lexical equivalence by Larson (1984) and the theory of componential analysis by Bell (1993). There are 100 name of Doraemon tools were found in these comics. Finding lexical equivalents in special problems are mostly found with 48 datas (48%) and lexical equivalents when concepts are shared with 44 datas (44%), the least is lexical equivalents when concepts are unknown with only 8 datas (8%). There were 58 datas (58%) where shift meaning occurred and 42 datas (42%) where shift meaning did not occurred. In conclusion, translator did a lot of adjustments in translation based on comic images, tools functions and target language so that the readers can easily understand the meanings.